Electrocardiographic Changes During Pregnancy at Third Trimester: A Comparative Study - Chaudhary, Sonam; saha, Chanchhu Gopal; Sarkar, Dipali (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: The cardiovascular system undergoes physiological changes during pregnancy. Electrocardiograms thereby play important role in understanding these physiological changes with the pathological one. The study has been carried out to study the electrocardiographic changes in pregnant women of third trimester and compare it with the non-pregnant women of same age group. Methods: Sixty third trimester pregnant women and sixty non-pregnant women of same age group attending Manipal Teaching Hospital were included. The 12 lead electrocardiograms of the participants were taken in supine position. The electrocardiograms were studied for various parameters like waves, intervals, segments and mean ventricular depolarization axis. Result: The result showed increase in heart rate in pregnant women when compared to control group. The decrease in PR interval associated with pregnancy was highly significant. The abnormalities in T wave associated with pregnancy, mostly in lead V1, V2, V3, V4, III and aVF were also highly significant. There was also increase occurrence of Q waves in pregnant women mostly in the bipolar leads. The QRS frontal axis compared to control showed increased tendency to shift towards left with advancing pregnancy. There was also significant increase in QT and QTc interval in third trimester pregnant women. The amplitude of various waves seemed to be decreased with pregnancy as well. Conclusion: This study shows that changes in electrocardiograms in third trimester pregnant women do occur. Therefore interpretation and evaluation of electrocardiograms in pregnancy should be done with caution.